A New Approach for Concept Drift Detection in Visual Data - Tran, Quang Tien (Springer Nature, 2024)
Lecture Notes in Networks and Systems (LNNS,volume 882); The 13th Conference on Information Technology and Its Applications (CITA 2024) ; pp: 172-183.